2017
DOI: 10.1016/j.stemcr.2017.04.012
|View full text |Cite
|
Sign up to set email alerts
|

SCA-1 Expression Level Identifies Quiescent Hematopoietic Stem and Progenitor Cells

Abstract: SummaryBlood cell generation depends on continuous cellular output by the sequential hierarchy of hematopoietic stem cell (HSC) and progenitor populations that all contain quiescent and actively cycling cells. Hematopoietic stem and progenitor cells (HSPCs) express the surface molecule Stem cell antigen 1 (SCA-1/LY6A). Using histone 2B-red fluorescent fusion protein label retention and cell-cycle reporter mice, we demonstrate that high SCA-1 expression (SCA-1hi) identifies not only quiescent HSCs but quiescent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 39 publications
2
36
0
1
Order By: Relevance
“…Previous studies have shown that Sca1 expression increases upon IFN-α exposure of LSKs (Essers et al, 2009; Morcos et al, 2017). Consistent with a defective IFN response upon loss of Jak1, Jak1-null hematopoietic cells failed to upregulate Sca1 surface expression in response to IFN-α secretion caused by a single injection of poly(I:C) in vivo (Figure 5B).…”
Section: Resultsmentioning
confidence: 97%
“…Previous studies have shown that Sca1 expression increases upon IFN-α exposure of LSKs (Essers et al, 2009; Morcos et al, 2017). Consistent with a defective IFN response upon loss of Jak1, Jak1-null hematopoietic cells failed to upregulate Sca1 surface expression in response to IFN-α secretion caused by a single injection of poly(I:C) in vivo (Figure 5B).…”
Section: Resultsmentioning
confidence: 97%
“…PB neutrophils (PMN, CD11b + Gr-1 hi ), B- (CD19 + ) and T-lymphocytes (CD3 + ) of secondary recipients ( n = 4/group) were analyzed for donor origin at indicated time points (right panel, mean and SD are shown, significance was calculated by repeated measures two-way ANOVA with Bonferroni post-test). (I) Maximum H2B-FP fluorescence intensities (as judged by the 99th percentile) of MPPs (LSK CD48 − /lo CD150 − ) isolated from chased R26 rtTA / Col1A1 H2B-RFP (shown in red; Säwén et al, 2016, dashed line, open circles; Morcos et al, 2017, continuous line, filled circles) or R26 rtTA/rtTA / Col1A1 H2B-GFP/H2B-GFP (green; same animals as in Fig. 2 A “GFP Morcos”) individual mice are depicted.…”
Section: Resultsmentioning
confidence: 99%
“…Mean frequencies and SD of LSK CD48 −/lo CD150 + cells are shown, except for data from Oguro et al (2013), in which a weighted mean of the HSC-1 and HSC-2 subpopulations was calculated ([1× HSC-1 + 3× HSC-2]/4). (B) Maximum H2B-FP fluorescence intensities (as judged by the 99th percentile) of HSCs (LSK CD48 −/lo CD150 + ) isolated from chased R26 rtTA / Col1A1 H2B-RFP (shown in red; Säwén et al, 2016, dashed line, open circles; Morcos et al, 2017, continuous line, filled circles) or R26 rtTA/rtTA / Col1A1 H2B-GFP/H2B-GFP (green; same animals as in A “GFP Morcos”) individual mice are depicted. The data were fitted by our mathematical model (see G), and loss of maximum fluorescence was attributed to H2B-FP degradation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations